Multiple Endocrine Adenoma Syndrome. Issue 1 (March 1960) - Cooke, W. T.; Fowler, D. I.; Gaddie, R.; Cox, E. V.; Meynell, M. J.; Brewer, D.
Abstract : The case history of a 40-year-old woman with a fatal haemorrhage from a duodenal ulcer, jejunitis, renal lithiasis, hypertrophy of the adrenal glands, multiple adenomas of the pancreas, and three adenomas of both the parathyroid and pituitary glands is reported. Though there was histological evidence, in the bones, of hyperparathyroidism, the serum levels of calcium, phosphorus, and phosphatase and the urinary excretion of calcium were normal. The significance of low calcium and high phosphorus excretion in the urine as an indication of parathyroid disorder is discussed. "Multiple endocrine adenoma syndrome" is suggested as the appropriate designation for the clinical disorders in which adenomas of one or more endocrine glands are associated with disorders of the alimentary tract when patients present with recurrent peptic ulceration, pancreatic dysfunction, or watery diarrhoea.